Exploring Campus Open Space Qualities: Identifying the U.P. Diliman Academic Core’s Predominant Qualities in its Physical, Social and Psychological Aspects - Sabido, Brian Alan L.; Ramos, Grace C. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 5, 2016)
The University of the Philippines (U.P.) Diliman is taking steps in its development towards a more self-sustaining community. Measuring the adequacy of the U.P. Diliman campus’ amenities is an important step towards this goal. This paper measures the adequacy of the Academic Core, as the central open space amenity of the U.P. Diliman Campus through a survey that aimed to identify its predominant qualities. The qualities identified served as indicators of how adequate the Academic Core is in meeting the needs of the Diliman community. Findings reveal that the Academic Core is predominantly grounds for passive recreation and the identified predominant qualities may provide insight and basis for design considerations in developing new amenities and enhancing existing ones in the process of planning a self-sustaining community.